THE LAW OF ATTRACTION DAN DOA DALAM ISLAM - Nurdin, Muhammad (IAIN Ponorogo, 2012)
Abstract: Many motivational books have been being present in the community who are entering the era of information and communication. One of the books that has influenced many titles of the other is the work of Rhonda Byrne The Secret. In this book it is revealed that “like attracts like.” Muslim readers could compare The Law of Attraction with prayers which become their daily rituals. This paper analyzes the Law of Attraction with all its rationale and explain it in the perspective of the concept of prayer in Islam. In this discussion it was found that the Law of Attraction could strengthen the confidence of the prayer of Muslim to God. There is a mechanism of natural processes and the influence of waves of thoughts and feelings in the prayer. The Law of Attraction teaches that man is responsible for his life, because man will reap what he is thinking and feeling. For this reason, it is not useful to blame God for misfortunes of human destiny. Terdapat banyak buku motivasi hadir dalam masyarakat yang sedang memasuki era informasi dan komunikasi. Salah satu buku yang mempengaruhi banyak judul-judul buku yang lain adalah The Secret karya Rhonda Byrne. Dalam buku ini diungkapkan bahwa like attracts like, kemiripan menarik kemiripan. Para pembaca Muslim dapat membandingkan antara The Law of Attraction dengan doa yang menjadi ritual mereka. Tulisan ini menganalisis The Law of Attraction dengan segala dasar pemikirannya dan menjelaskannya dengan konsep doa dalam Islam. Dalam pembahasan ini ditemukan bahwa The Law of Attraction dapat memperkokoh keyakinan akan keterkabulan doa kepada Allah. Bahwa ada mekanisme, proses alam, pengaruh gelombang pikiran dan perasaan dalam keterkabulan doa. The Law of Attraction juga mengajarkan bahwa manusia bertanggungjawab dalam kehidupannya, karena manusia menuai apa yang ia pikirkan dan rasakan. Untuk itulah, tidak bermanfaat menyalahkan Tuhan karena adanya kemalangan nasib manusia. Keywords: law of attraction, doa Islam, motivasi